Effect of Texturing Environment on Wetting of Biomimetic Superhydrophobic Surfaces Designed by Femtosecond Laser Texturing - Salomé Basset; Guillaume Heisbourg; Alina Pascale-Hamri; Stéphane Benayoun; Stéphane Valette (Nanomaterials, 2022)
Inspired by Euphorbia leaves, micrometric pillars are designed on 316L stainless steel surfaces using a femtosecond laser to achieve superhydrophobicity. In this study, we focus on wetting behavior evolution as a function of time and chemical environment. Two types of texturing designs are performed: the laser texturing of micrometric square pillars, and the laser texturing of micrometric square pillars whose tops were irradiated using various fluences to obtain a different topography on the nanometric scale. Two laser texturing environments are considered in both cases: a CO2 flow and ambient air. The main result is that 250 days after laser texturing, steady-state contact angles (SSCA) were above 130° no matter what the environment was. We also study the effect of regular wetting over time. Comparing the results of surfaces for which wetting over time was conducted and that of the undisturbed surfaces for 250 days demonstrates that performing wetting measurements when the surface is not stable led to major changes in droplet behavior. Our surfaces have a unique wettability in which droplets are in an intermediate state. Finally, using a CO2 flow did not help reach higher SSCA, but it limited the effect of regular wetting measurements.